2004
DOI: 10.1107/s1600536804011699
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitroso-2-phenylimidazo[1,2-a]pyrimidine

Abstract: Key indicatorsSingle-crystal X-ray study T = 173 K Mean '(C±C) = 0.004 A Ê R factor = 0.054 wR factor = 0.140 Data-to-parameter ratio = 11.9For details of how these key indicators were automatically derived from the article, see http://journals.iucr.org/e. # 2004 International Union of Crystallography Printed in Great Britain ± all rights reserved The title compound, C 12 H 8 N 4 O, is of pharmacological interest. It contains an imidazo[1,2-a]pyrimidine heterocycle, carrying a nitroso group in position 3 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The table omits structures with significant disorder and R factors greater than 6%, because their low precision does not allow detailed analysis of geometric features. Moreover, structures of electron-rich heteroaromatic nitroso compounds are also omitted, because their key features resemble those of nitrosobenzene derivatives and they add little to the basic understanding of how substituents interact with the nitroso group. Specific electron-rich heteroaromatic nitroso compounds for which structural data are available include derivatives of benzothiazole, benzothiophene, imidazopyrimidine, indolizine, and pyrazole. In addition, the structures of over 60 related derivatives of 5-nitrosopyrimidine have been published in the last two decades. The marked interest in this family of compounds mainly stems from their biological activity , and their use as intermediates in the synthesis of biologically relevant heterocycles. …”
Section: Structures Of Nitrosoarenes and Their Azodioxy Dimersmentioning
confidence: 99%
“…The table omits structures with significant disorder and R factors greater than 6%, because their low precision does not allow detailed analysis of geometric features. Moreover, structures of electron-rich heteroaromatic nitroso compounds are also omitted, because their key features resemble those of nitrosobenzene derivatives and they add little to the basic understanding of how substituents interact with the nitroso group. Specific electron-rich heteroaromatic nitroso compounds for which structural data are available include derivatives of benzothiazole, benzothiophene, imidazopyrimidine, indolizine, and pyrazole. In addition, the structures of over 60 related derivatives of 5-nitrosopyrimidine have been published in the last two decades. The marked interest in this family of compounds mainly stems from their biological activity , and their use as intermediates in the synthesis of biologically relevant heterocycles. …”
Section: Structures Of Nitrosoarenes and Their Azodioxy Dimersmentioning
confidence: 99%
“…For the medical properties of imidazo[1,2-a]pyrimidine derivatives, see: An et al (2009); Kim et al (2011); Linton et al (2011). For related structures, see: Yang et al (2008); Anaflous et al (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…Imidazo[1,2-a]pyrimidine derivatives have been used for treatment of cancers (An et al, 2009;Kim et al, 2011;Linton et al, 2011), and some analogues were reported (Anaflous et al, 2004;Yang et al, 2008). The title compound was synthesized by the reaction of 1-(2-methylimidazo[1,2-a]pyrimidin-3-yl)ethanone with 1,1-dimethoxy-N,N-dimethylmethanamine, and its crystal structure was confirmed by single crystal X-ray analysis (Fig.…”
Section: Data Collectionmentioning
confidence: 99%
“…Functionalized imidazo[1,2-a]pyrimidines (IPM) are of great interest with regard to their potential biological activities (Ana¯ous et al, 2004). Antimicrobial screening of imidazo[1,2-a]pyrimidine derivatives has been undertaken.…”
Section: Commentmentioning
confidence: 99%